Multilevel Self-Management in Nursing Research: An Approach to Decrease Health Disparities in Chronic Diseases - Iriarte, Evelyn; Cianelli, Rosina; Fernandez-Pineda, Madeline (Investigación y Educación en Enfermería, 2023)
Objective. To discuss multilevel self-management intervention research in nursing to decrease health disparities among people living with chronic diseases. Content synthesis. Multilevel interventions have become the core of nursing research in the last decade. However, a critical limitation of existing interventions targeting health disparities among those living with chronic diseases is the tendency to address single or individual-level factors solely. Conclusions. Nursing research iscreating knowledge that may be translated into clinical practice and promoting evidence-based and innovative self-management practices to decrease health disparities and promote health equity among people living with chronic diseases.